Muslims in Spain, 1492-1814 Living and Negotiating in the Land of the Infidel - Martín-Corrales, Eloy (Mediterranean Reconfigurations, 2020)
In Muslims in Spain, 1492-1814: Living and Negotiating in the Land of the Infidel, Eloy Martín-Corrales surveys Hispano-Muslim relations from the late fifteenth to the eighteenth centuries, a period of chronic hostilities. Nonetheless there were thousands of Muslims in Spain at that time: ambassadors, exiles, merchants, converts, and travelers. Their negotiating strategies, and the necessary support they found on both shores of the Mediterranean prove that relations between Spaniards and Muslims were based on reasons of state and on a pragmatism that generated intense political and economic ties.These increased enormously after the peace treaties that Spain signed with Muslim countries between 1767 and 1791. Readership: Of interest for the history of the political, diplomatic, economic, and cultural relations between Spain and Muslim countries of the Maghreb and Middle East in the Early Modern Age.